Significance of Serum Alkaline Phosphate and Lactate Dehydrogenase on Diagnosis and Prognosis of Gastrointestinal Cancer - Yadav, Dr. Pratibha (International Journal of Innovative Research in Medical Science, 2017)
The roles of enzymes especially alkaline phosphate (ALP), lactate dehydrogenase (LDH) in carcinogenesis in relation to disease activity have shown useful in estimating the extent and prognosis of malignant tumor in the digestive organ. Keeping this in consideration, the study was conducted on 140 subjects either sex out of which 35 normal adults and 105 gastrointestinal (GI) cancer patients. The follow up study was further undertaken and values of serum ALP and LDH of the same patients before and after surgery were recorded. The study showed that higher elevation of serum ALP levels in gastric malignancy than normal control group. Similarly LDH level in different GI cancer patients increased significantly (p <0.01) than the normal control group. The study suggests that levels of ALP and LDH can be used for monitoring the success of treatments as well they would be useful indicators for diagnoses and prognoses of gastrointestinal cancer.